MUSICAL SETTINGS OF A LYRICAL INSPIRATION – „NUR WER DIE SEHNSUCHT KENNT” BY JOHANN WOLFGANG VON GOETHE - Mateva, Elvira (E-Journal VFU, 2025)
A significant aspect of mastering vocal works lies in the conscious interpretation and profound understanding of the enduring union between text and music. In this context, the present article examines the impact of the poem „Nur wer die Sehnsucht kennt” from Johann Wolfgang von Goethe’s novel Wilhelm Meister on a number of composers from the late 18th and 19th centuries. It presents various musical interpretations of the poem by composers such as Beethoven, Schubert, Schumann, Tchaikovsky, and Medtner, highlighting their distinctive stylistic and emotional characteristics.
Keywords: „Nur wer die Sehnsucht kennt“; Johann Wolfgang von Goethe; Wilhelm Meister; vocal interpretation; Beethoven; Schubert; Schumann; Tchaikovsky; Medtner